2019
DOI: 10.5146/tjpath.2019.01472
|View full text |Cite
|
Sign up to set email alerts
|

Metaplastic carcinoma of the breast: analysis of 38 cases from a single institute

Abstract: Objective: To evaluate the pathological and radiological features, hormone profiles, surgery and treatment methods of metaplastic breast carcinoma cases diagnosed at our center in the light of current literature. Material and Method: A total of 38 metaplastic breast cancer cases diagnosed between 2006-2018 at our center were included in the study. The patients were evaluated in terms of age, tumor size, localization, histological grade, hormone profiles (ER, PR, Her2-neu), American Joint Committee on Cancer (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 23 publications
2
14
0
1
Order By: Relevance
“…The current study reported 64.3% of the patients were high grade. This corresponds to the findings of previous studies, which documented significantly higher histological grading of MBC (75–100%) [ 2 , 5 , 6 , 8 , 11 ]. When compared with invasive ductal carcinoma, MBC also showed preponderance towards high histological grading (68.4% vs 34.5%, p=<0.001) [ 4 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The current study reported 64.3% of the patients were high grade. This corresponds to the findings of previous studies, which documented significantly higher histological grading of MBC (75–100%) [ 2 , 5 , 6 , 8 , 11 ]. When compared with invasive ductal carcinoma, MBC also showed preponderance towards high histological grading (68.4% vs 34.5%, p=<0.001) [ 4 ].…”
Section: Discussionsupporting
confidence: 92%
“…This classification has been widely adopted in multiple studies in the past, including our current study. Our case series reported that squamous cell carcinoma is the most common histological subtype (42.9%), which corresponds to the findings of several studies, with documented incidence ranging between 26 and 48% [ [5] , [6] , [7] , [8] ]. Schroeder et al which included a total of 1516 cases of MBC in the United States, documented the most common histological type was metaplastic carcinoma of no specific type (81.9%) [ 4 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…1,4 Inadequate sampling can lead to misdiagnosis on core needle biopsy and fine-needle aspiration cytology. 7 The sarcomatous component of MBCs can resemble other spindle cell neoplasms like malignant phyllodes, fibrosarcoma, myoepithelial carcinoma, malignant fibrous histiocytoma, etc. Adequate sampling also helps find the DCIS component which, is strongly supportive of metaplastic carcinoma, thus, avoiding misinterpretation.…”
Section: Discussionmentioning
confidence: 99%
“…Adequate sampling also helps find the DCIS component which, is strongly supportive of metaplastic carcinoma, thus, avoiding misinterpretation. 7 Definitive diagnosis of MBC can appropriately be made on excisional biopsy specimens. 1 Immunohistochemical confirmation of tumor epithelial component is necessary for the diagnosis of metaplastic carcinoma.…”
Section: Discussionmentioning
confidence: 99%